2011
DOI: 10.3389/fmicb.2011.00159
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Antimicrobial Peptide and Polymyxin B Resistance in the Genus Burkholderia

Abstract: Cationic antimicrobial peptides and polymyxins are a group of naturally occurring antibiotics that can also possess immunomodulatory activities. They are considered a new source of antibiotics for treating infections by bacteria that are resistant to conventional antibiotics. Members of the genus Burkholderia, which includes various human pathogens, are inherently resistant to antimicrobial peptides. The resistance is several orders of magnitude higher than that of other Gram-negative bacteria such as Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 91 publications
1
68
0
Order By: Relevance
“…B. multivorans is highly resistant to both fosmidomycin and polymyxins (5,26). To determine if the growth of B. multivorans can be synergistically inhibited by treatment with a combination of colistin and fosmidomycin, initial MIC checker- To determine if the potentiating effect of fosmidomycin was specific for colistin, other antimicrobial classes that perturb the bacterial membrane were tested in concert with fosmidomycin for inhibition of B. multivorans growth ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. multivorans is highly resistant to both fosmidomycin and polymyxins (5,26). To determine if the growth of B. multivorans can be synergistically inhibited by treatment with a combination of colistin and fosmidomycin, initial MIC checker- To determine if the potentiating effect of fosmidomycin was specific for colistin, other antimicrobial classes that perturb the bacterial membrane were tested in concert with fosmidomycin for inhibition of B. multivorans growth ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Bcc bacteria are ominous CF pathogens because of their potential to cause rapid clinical deterioration and death (3). The major challenge to clinical therapy of Bcc pulmonary infections is their innate resistance to a broad range of antimicrobials, including polycationic agents that are typically used to treat other CF pulmonary pathogens (5). Although Burkholderia cenocepacia has widely been considered the most prevalent and virulent Bcc species in CF infections, the proportion of B. multivorans infections is increasing (6), with its incidence in CF patients now exceeding that of B. cenocepacia in the United States and Canada (7,8).…”
mentioning
confidence: 99%
“…The Ara4N modification of lipid A is a regulated mechanism exploited by many Gram negative bacteria to resist cationic antimicrobial peptide, and under most growth conditions this modification is dispensable (Kawasaki et al, 2005; Lewenza et al, 2005; Loutet and Valvano, 2011; Lin et al, 2014). Hamad et al (2012) demonstrated that Ara4N served as a recognition signal for the transport of LPS to the outer membrane through the Lpt pathway, consolidating the essential role of this aminoarabinose in determining the architecture of the outer membrane in B. cenocepacia .…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia spp. are human pathogens associated with opportunistic infections in cystic fibrosis patients and chronic granulomatous disease (230). The high level AMP resistance exhibited by this Genus has been attributed to the constitutive incorporation of L -Ara4N into the LPS molecule (230, 231).…”
Section: Bacterial Amp Resistance Mechanismsmentioning
confidence: 99%
“…are human pathogens associated with opportunistic infections in cystic fibrosis patients and chronic granulomatous disease (230). The high level AMP resistance exhibited by this Genus has been attributed to the constitutive incorporation of L -Ara4N into the LPS molecule (230, 231). Alternative sigma factor RpoE coordinates Burkholderia gene expression under stress conditions and contributes to AMP resistance in a temperature-dependent manner (230, 232).…”
Section: Bacterial Amp Resistance Mechanismsmentioning
confidence: 99%